THE ROLE OF LABOR FORCE MIGRATION AND SOCIO-ECONOMIC CONSEQUENCES IN ARMENIA (International Journal of Innovative Technologies in Economy, 2018)
Labor migration currently is the most important migratory flow of the world. International labor migration is conditioned by economic and non-economic factors. If considering the emigration as a factor relaxing the tense in internal labor market, then at the present stage of social and economic development, the loss of potential of highly skilled professionals and workers, in the near future may cause a serious problem of unsatisfied demand for human capital. In a country of mass emigration, "the equivalent” of the loss of human capital, becomes migrant remittances. Of course, especially in countries forming new markets in the process of socio-economic development, remittances play an important and enough active role. As a factor of socio- economic development, remittances of population in the order of importance, come second after direct investments, as a source of external financing. They have a huge impact on the domestic labor market, private consumption, imports, the state budget and other sectors of socio-economic relations. Ultimately, this contributes so that incomes received from abroad were spent at home on more progressive and civilized forms of consumption, and in the future increased investment activity, and decrease the poverty level.